Determination of the dose and time dependent toxicological effects of hydroalcoholic extract of Terminalia catappa kernel on the renal functions parameters of wister rats - Batubo, Nimisoere P. (International Journal of Research in Medical Sciences, 2018)
Background: The use of herbal medications has been implicated to cause renal toxicity and failure. Terminalia catappa has been used in ancient tradition in the treatment several diseases. This study aimed to determine the dose and time related effects of the hydroalcoholic extract of Terminalia catappa on the renal functions of Wister rats following long time period of administration. Methods: Forty female Wister rats were used as experimental animals and equally divided into 5 groups. The hydroalcoholic extract of Terminalia catappa were administered on the experimental animals for 42 days. Three groups were treated orally with three different doses of Terminalia catappa hydroalcoholic extract; 0.5g/kg, 1.0g/kg and 3.0g/kg respectively while another two groups as control. Signs of toxicity in the experimental rats were determined by the number of death, nutritional behaviour and physiological characteristics of the animal by observation while blood sample was collected for the determination of renal functions parameters. Results: No death was recorded in all test groups during the period of the study. The nutritional behaviour of the rats was not affected and no abnormalities in the physiological characteristic of the rats were detected. The renal functions parameters (Na+, K+, Cl-, HCO3-, Urea, Uric acid and Creatinine) were not significantly (p>0.05) altered. Conclusions: Based on the results, it can be concluded that there were no nephrotoxic effects of hydroalcoholic extract of Terminalia catappa on Wister rats and therefore it can be said to have a wide margin of safety for use and consumption.